Mass gatherings contributed to early COVID-19 spread: Evidence from US sports - Ahammer Alexander; Halla Martin; Mario Lackner (Johannes Kepler Universität Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2020)
Social distancing is important to slow the community spread of infectious disease, but it creates enormous economic and social cost. It is thus important to quantify the benefits of different measures. We study the ban of mass gatherings, an intervention with comparably low cost. We exploit exogenous spatial and temporal variation in NBA and NHL games, which arise due to the leagues' predetermined schedules, and the suspension of the 2019-20 seasons. This allows us to estimate the impact of these mass gatherings on the spread of COVID-19 in affected US counties. One additional mass gathering increased the cumulative number of COVID-19 deaths in affected counties by 11 percent.
Keywords: I18; H12; I10; 330; social distancing; mass gatherings; Coronavirus Disease 2019; COVID-19